The Fulfillment of Hierarchy of Needs of Elinor in The "Sense And Sensibility" Novel by Jane Austen: A Study of Humanism Psychology of Abraham Maslow - Imam Ghozali (Pancaran Pendidikan, 2020)
This research was intended to find and describe the fulfillment of hierarchy of needs of Elinor in the “Sense and Sensibility” by Jane Austen which mostly about the story of Dashwood family, Elinor and Marianne Dashwood. The story began with their father’s death, Henry Dashwood. He left only a small fortune to Elinor, Marianne, their mother and younger sister, while most of Dashwood's wealth and property were handed over to John, Henry's son from his previous marriage. Elinor's struggles to fulfill her needs began with discomfort that occurred in her family. The method used was a qualitative descriptive, in which the data were in the form of words, sentences, and paragraphs that identified the fulfillment of hierarchy of needs. The data source was the "Sense and Sensibility" novel by Jane Austen and the data collection techniques were reading and note-taking. The data were analyzed by identifying, classifying, describing and drawing conclusions. The results and discussion in this article showed that in fulfilling her physiological, safety, love and belonging, and esteem needs, Elinor faced struggles and twist and turn. Those four needs were found sequentially in the story, but the need for self-actualization had not been reflected in the novel.